Advances in the interaction between lumbar intervertebral disc degeneration and fat infiltration of paraspinal muscles: critical summarization, classification, and perspectives - Jiang, Jiaqiu; Huang, Yilong; He, Bo (Frontiers in Endocrinology, 2024)
More than 619 million people in the world suffer from low back pain (LBP). As two potential inducers of LBP, intervertebral disc degeneration (IVDD) and fat infiltration of paraspinal muscles (PSMs) have attracted extensive attention in recent years. So far, only one review has been presented to summarize their relationship and relevant mechanisms. Nevertheless, it has several noticeable drawbacks, such as incomplete categorization and discussion, lack of practical proposals, etc. Consequently, this paper aims to systematically summarize and classify the interaction between IVDD and fat infiltration of PSMs, thus providing a one-stop search handbook for future studies. As a result, four mechanisms of IVDD leading to fat infiltration of PSMs and three mechanisms of fat infiltration in PSMs causing IVDD are thoroughly analyzed and summarized. The typical reseaches are tabulated and evaluated from four aspects, i.e., methods, conclusions, benefits, and drawbacks. We find that IVDD and fat infiltration of PSMs is a vicious cycle that can promote the occurrence and development of each other, ultimately leading to LBP and disability. Finally, eight perspectives are proposed for future in-depth research.